Assessing The Role of Agricultural People’s Business Credit (KUR) in Enhancing Productivity in Indonesia’s Rice Farming: Evidence From The ACF Approach - Theresia Wahyuni; Riyanto (School of Business, Bogor Agricultural University (SB-IPB), 2026)
Background: Indonesia continues to face persistent rice productivity challenges that differ across regions. Conventional econometric approaches often fail to properly address endogeneity and simultaneity issues, leading to biased assessments of policy effectiveness. To overcome these limitations, this study applies the Ackerberg–Caves–Frazer (ACF) method to panel data from 32 provinces (2016–2023) to obtain reliable estimates of Total Factor Productivity (TFP) and quantify the true contribution of the Agricultural People's Business Credit (KUR) toward efficiency improvement and technology adoption.Purpose: The main objective is to generate consistent input elasticity estimates and accurately measure TFP in Indonesia’s rice sector, enabling a more credible assessment of how KUR influences production performance and efficiency across provinces.Design/methodology/approach: Using a quantitative two-stage ACF–TFP estimation framework, the analysis shows that KUR significantly enhances rice productivity, primarily through TFP gains rather than increases in input quantities. Regional disparities are substantial, with western provinces demonstrating higher efficiency than eastern provinces. Input elasticities are relatively small, indicating diminishing factor responsiveness. The Wald Test rejects the hypothesis of Constant Returns to Scale (∑β=1), confirming scale inefficiencies, particularly in low-TFP regions. These findings underscore that productivity gains are driven by efficiency rather than quantity.Findings/Results: (1) TFP varies widely across provinces, (2) Efficiency levels are consistently higher in the western region, (3) Low or negative TFP values indicate suboptimal use of KUR and other inputs, and (4) Scale inefficiencies persist, reflecting structural and managerial constraints in rice farming systems.Conclusion: Policy design should move from uniform, input-driven support toward a targeted productivity-based approach. Integrating KUR financing with technical assistance and region-specific strategies, such as technological upgrading, efficiency improvement, and scale consolidation, can help reduce interregional TFP gaps and strengthen the sustainability of rice farming.Originality/value (State of the art): This study offers a methodological advancement by applying the ACF approach, commonly used in industrial economics, to agricultural productivity evaluation. The model effectively mitigates endogeneity bias and provides a more accurate measurement of TFP, offering new insights into how financing instruments influence efficiency in Indonesia’s rice sector Keywords: financing efficiency, ackerberg-caves-frazer, people’s business credit, productivity, rice farming